2009
DOI: 10.2741/3237
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor modulates the tumorigenic potential of melanoma

Abstract: Potential contribution of the Epidermal Growth Factor Receptor (EGFR) in melanoma immunobiology remains unclear, in part due to a lack of experimental models. We demonstrated previously that B16F10 melanoma transfected with the full length cDNA of the human EGFR increases the tumor cell proliferation in vitro. To further study its contribution in vivo, EGFR-transfected B16F10 cells were inoculated in syngenic C57BL/6 mice and its tumorigenic capacity was compared with the parental melanoma. Contrary to the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Together with the paucity of driver EGFR mutations in melanoma, such results have dampened preclinical enthusiasm for EGFR as a target in this malignancy. In fact, one recent study found that EGFR expression may modestly suppress melanoma growth in a B16 model (Diaz et al 2009). …”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…Together with the paucity of driver EGFR mutations in melanoma, such results have dampened preclinical enthusiasm for EGFR as a target in this malignancy. In fact, one recent study found that EGFR expression may modestly suppress melanoma growth in a B16 model (Diaz et al 2009). …”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…This is in contrast to in vivo studies using implantation of melanoma cells, where decreased EGFR together with growth inhibition have been documented. It seems that EGFR levels are modulated during melanoma growth, with one of important modulators being the immune system (Diaz et al, 2009). EGFR is increased not only in melanoma lesions including both early-and late-stage melanomas but also in benign nevi.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%